2023
DOI: 10.2106/jbjs.22.01218
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief After Total Knee Arthroplasty with Intravenous and Periarticular Corticosteroid

Abstract: Background:Total knee arthroplasty (TKA) is a cost-effective procedure, but it is also associated with substantial postoperative pain. The present study aimed to compare pain relief and functional recovery after TKA among groups that received intravenous corticosteroids, periarticular corticosteroids, or a combination of both.Methods:This randomized, double-blinded clinical trial in a local institution in Hong Kong recruited 178 patients who underwent primary unilateral TKA. Six of these patients were excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Total joint arthroplasty represents a highly efficacious intervention for end‐stage hip or knee disease, and perioperative corticosteroids, as part of contemporary multimodal treatment regimens, are often administered in order to relieve postoperative pain, reduce the risk of postoperative complications, and enhance recovery. 1 Numerous randomized controlled trials 2 , 3 and meta‐analyses 4 , 5 , 6 , 7 have consistently demonstrated that perioperative glucocorticoids can significantly reduce postoperative pain, opioid use, nausea, and vomiting without increasing risk of postoperative complications. However, most of these studies have focused on patients with osteoarthritis of hip or knee other than rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Total joint arthroplasty represents a highly efficacious intervention for end‐stage hip or knee disease, and perioperative corticosteroids, as part of contemporary multimodal treatment regimens, are often administered in order to relieve postoperative pain, reduce the risk of postoperative complications, and enhance recovery. 1 Numerous randomized controlled trials 2 , 3 and meta‐analyses 4 , 5 , 6 , 7 have consistently demonstrated that perioperative glucocorticoids can significantly reduce postoperative pain, opioid use, nausea, and vomiting without increasing risk of postoperative complications. However, most of these studies have focused on patients with osteoarthritis of hip or knee other than rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%